Neolithic domesticity and other prehistoric anomalies: excavations at Laigh Newton, East Ayrshire - Toolis, Ronan; Bacon, Jo; Ballin, Torben Bjarke; Smith, Beverley Ballin; Carruthers, Martin; Francoz, Charlotte; James, Heather; McLellan, Kirsteen; McSwan, Gillian; Ramsay, Susan; et al. (Scottish Archaeological Internet Reports, 2011)
A series of archaeological evaluations and excavations at Laigh Newton in East Ayrshire (NGR: NS 5937 3684) revealed evidence for intermittent occupation of this valley terrace between the Mesolithic and the Late Iron Age. The plough-truncated archaeology included the remains of a rectangular building and associated features of the mid-late 4th millennium BC, a more ephemeral structure and related pits of the mid-3rd millennium BC, a charcoal-burning pit of the mid-1st millennium AD and two other rectilinear structures of indeterminate date.